Elite professional golfers` physical preparation practices and perceptions - White, S. R.; Coughlan, D. A.; Wood, C.; Wells, J. E. T.; Murray, A.; Brearley, S. L.; Moran, J. (International Journal of Sports Science & Coaching, 2025)
Physical preparation for improving golf performance is a topic of rising interest. However, little is known of how advancements in empirical evidence have integrated with the practices and perceptions of elite professional golfers. To address this shortfall in knowledge, forty-nine (n = 32 European Tour, n = 17 Challenge Tour) professional golfers were surveyed on their physical preparation practices and perceptions. Additionally, golfers` in-tournament training practices were observed at the 148th Open Championship gym facility. The majority of surveyed golfers had experience of following a "structured resistance training plan" (89.8%). However, players face challenges to incorporate physical preparation throughout a tournament year. In turn, the development of physical attributes including muscular strength, power and muscle mass known to underpin clubhead speed/driver distance, and the training methods typically required to stimulate such adaptations were often not prioritised during the in-season period. Limited engagement with heavy load and high-velocity resistance training methods were observed at the Open Championship. However, in order to maximise their potential, players can enhance key physical qualities on a year-round basis (i.e., during the in-season). Consequently, further education and research on how to effectively organise and optimise resistance training within tournament constraints would be of value.